St Gregory's Minster, Kirkdale, North Yorkshire : archaeological investigations and historical context - Rahtz, Philip A. (Archaeopress Archaeology, 2021)
The result of c. 20 years of work on and around the church of St Gregory's Minster, Kirkdale, North Yorkshire, this work is concerned primarily with the 8th century onwards, but also extends the time-period of this isolated site, particularly for the post-Roman to middle Saxon period, but also as an earlier probably religious landscape.